A taxonomy of firm-level IPR application practices to inform policy debates - Marcel Seip; Carolina Castaldi; Meindert Flikkema; Ard-Pieter De Man (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Current debates on the social returns of Intellectual Property Right (IPR) systems deal with the presumed negative effects of two practices: IPR bundling and the strong concentration of IPRs in certain firms and industries. These debates are hampered by the lack of empirical evidence on IPR application practices. This study presents unique and comprehensive data about firm-level IPR application practices in the Netherlands. We develop a taxonomy based on the firm-level variety and intensity of IPR applications. We identify five archetypes of IPR applicants: patent rookies, trademark rookies, IPR strategists, IPR specialists and IPR generalists. Our findings show that a few large firms in high-tech industries combine high IPR application variety and high IPR application intensity. However, high variety is also associated with low intensity and low variety with high intensity. For a large majority of the firms, IPR application is equivalent to single trademark application or the ad hoc application of another IPR. We discuss the implications of our findings for current IPR debates and for further research.
Keywords: O34; O39; 330; Intellectual property rights; taxonomy; policy